Pragmatic RAndomised controlled trial of a trauma-focused guided self-help Programme versus InDividual trauma-focused cognitive Behavioural therapy for post-traumatic stress disorder (RAPID): trial protocol - Nollett, C; Lewis, C; Kitchiner, N; Roberts, N; Addison, K; Brookes-Howell, L; Cosgrove, S; Cullen, K; Ehlers, A; Heke, S; Kelson, M; Lovell, K; et al. (BioMed Central, 2018)
There is good evidence that trauma-focused therapies for Post-Traumatic Stress Disorder are effective. However, they are not always feasible to deliver due a shortage of trained therapists and demands on the patient. An online trauma-focused Guided Self-Help (GSH) programme which could overcome these barriers has shown promise in a pilot study. This study will be the first to evaluate GSH against standard face-to-face therapy to assess its suitability for use in the NHS.The study is a large-scale multi-centre pragmatic randomised controlled non-inferiority trial, with assessors masked to treatment allocation. One hundred and ninety-two participants will be randomly allocated to receive either face-to-face trauma-focused cognitive behaviour therapy (TFCBT) or trauma-focused online guided self-help (GSH). The primary outcome will be the severity of symptoms of PTSD over the previous week as measured by the Clinician Administered PTSD Scale for DSM5 (CAPS-5) at 16 weeks post-randomisation. Secondary outcome measures include PTSD symptoms over the previous month as measured by the CAPS-5 at 52 weeks plus the Impact of Event Scale - revised (IES-R), Work and Social Adjustment Scale (WSAS), Patient Health Questionnaire-9 (PHQ-9), General Anxiety Disorder-7 (GAD-7), Alcohol Use Disorders Test (AUDIT-O), Multidimensional Scale for Perceived Social Support (MSPSS), short Post-Traumatic Cognitions Inventory (PTCI), Insomnia Severity Index (ISI) and General Self Efficacy Scale (GSES) measured at 16 and 52 weeks post-randomisation. Changes in health-related quality of life will be measured by the EQ-5D and the level of healthcare resource utilisation for health economic analysis will be determined by an amended version of the Client Socio-Demographic and Service Receipt Inventory European Version. The Client Satisfaction Questionnaire (CSQ) will be collected at 16 weeks post-randomisation to evaluate treatment satisfaction.This study will be the first to compare online GSH with usual face-to-face therapy for PTSD. The strengths are that it will test a rigorously developed intervention in a real world setting to inform NHS commissioning. The potential challenges of delivering such a pragmatic study may include participant recruitment, retention and adherence, therapist retention, and fidelity of intervention delivery.ISRCTN13697710 registered on 20/12/2016.